The Substance Evaluation Study of Construction Safety Plan Implementation and It's Implementation - Yunus, Febriyani; Suraji, Akhmad; Ophiyandri, Taufika (CIVED, 2024)
Padang State University has experienced rapid student enrollment growth, driving the need for new infrastructure. Most of the buildings have more than 3 floors, and one of the ongoing projects reaches a height of 32.05 meters with 6 floors, contributing to higher construction risks. This research was conducted to evaluate the implementation of Construction Safety Plans (CSP) on projects over the past two years in accordance with the Ministry of Public Works and Housing Regulation No. 10 of 2021 and the Circular Letter of the Ministry of Public Works and Housing No. 10 of 2022. Data collection methods for this study involved two approaches: compliance audits and performance audits. Compliance audits involved document-based inspections of CSP, while performance audits included on-site observations and project work evaluations. The research results revealed that the construction of the central information and library building achieved the highest CSP implementation rate, with compliance rates of 93.33% in compliance audits and 91.42% in performance audits. In contrast, the rehabilitation project for the Faculty of Sports Sciences and the Dean's office showed lower compliance rates, scoring 37.14% in compliance audits and 35.34% in performance audits. The study also found that project contract values correlated with CSP compliance levels. Higher contract values were associated with higher CSP compliance. Contractor qualifications also played a crucial role in ensuring compliance with safety regulations. Based on these findings, it is recommended that UNP exercise greater selectivity in contractor selection processes. This study highlights the importance of construction safety in construction projects.